The Role of Brand Awareness in Mediating the Effect of Message Appeals in Media Advertising on Purchase Intention - Faizul Muadzin; Sari Lenggogeni (Benefit: Jurnal Manajemen dan Bisnis, 2021)
Abstract: Competition in telecommunications industry makes industry players look for various ways to get awareness from consumers, one of which is by approaching them through advertising or advertising with the message appeals method that is attracti ve to consumers. The purpose of this study is to determine the message appeald in influencing the purchase intention of XL Axiata prepaid data card users in West Sumatra. The calculation of the number on samples using the Slovin formula with a total sample size of 400 and the sampling of districts / cities from the total sample using cluster random sampling. The collected data were analyzed using the Structural Equation Model (SEM) for all variables. The findings indicate that there is no significant rational appeals effect on purchase intention. Emotional has a significant effect on purchase intention. Rational has a significant effect on brand awareness. Emotional has a significant effect on brand awareness. Brand awareness has a significant effect on purchase intention